Novel Thioethers of Dihydroartemisinin Exhibiting Their Biological Activities - Ngoc Hung Truong; Thi Hong Ha Tran; Kim Chi Hoang; Duc Bao Ninh; Viet Duc Le; Duc Anh Le; Van Chinh Luu (Heteroatom Chemistry)
Eleven conjugates between dihydroartemisinin (DHA) with thiols containing both ether and thioether bonds were designed, synthesized by a two-step procedure including etherification and S-alkylation. Analysis of the NMR spectral data indicated that the dimer of DHA with thiols 6-mercaptopurine and 2-mercaptoimidazole was produced with yields of 31% and 62%, respectively. Furthermore, the tautomerization of thiol 5-methoxy-2-mercaptobenzimidazole led to the formation of a mixture of two isomers in which they might be interchangeable through a dynamic tautomeric equilibrium in the solution. Screening in vitro biological activities revealed that most of the synthesized conjugates showed good cytotoxic and anti-inflammatory activity, while three of them displayed α-glucosidase inhibitory activity. Notably, two conjugates 5d and 5e of DHA with thiols 2-mercaptopyrimidine and 2-mercaptobenzothiazole had an effect in all tested activities in which conjugate 5e is the most potent.